2019
DOI: 10.1093/infdis/jiz123
|View full text |Cite
|
Sign up to set email alerts
|

Increased CXCR3+ T Cells Impairs Recruitment of T-Helper Type 17 Cells via Interferon γ and Interleukin 18 in the Small Intestine Mucosa During Treated HIV-1 Infection

Abstract: The restoration of CD4+ T cells, especially T-helper type 17 (Th17) cells, remains incomplete in the gut mucosa of most human immunodeficiency virus type 1 (HIV-1)–infected individuals despite sustained antiretroviral therapy (ART). Herein, we report an increase in the absolute number of CXCR3+ T cells in the duodenal mucosa during ART. The frequencies of Th1 and CXCR3+ CD8+ T cells were increased and negatively correlated with CCL20 and CCL25 expression in the mucosa. In ex vivo analyses, we showed that inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…In line with our findings, no differences in CCR6 + CD8 T-cell frequencies between SIV/HIV-infected and uninfected subjects have been reported ( 55 , 56 ). Similar to our data, increased frequencies of CXCR3 + CD8 T cells in both the blood and peripheral LNs have been reported during acute infection, which then decrease with disease progression ( 57 , 58 ). In addition, Wacleche et al proposed that CD8 T-cell recruitment to the GALT was mainly dependent upon integrin β7 and chemokine receptor CXCR3, while a limited CD4 and CD8 T-cell colocalization mediated by CCR6-dependent recruitment could contribute to poor viral control of the infection ( 59 ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, no differences in CCR6 + CD8 T-cell frequencies between SIV/HIV-infected and uninfected subjects have been reported ( 55 , 56 ). Similar to our data, increased frequencies of CXCR3 + CD8 T cells in both the blood and peripheral LNs have been reported during acute infection, which then decrease with disease progression ( 57 , 58 ). In addition, Wacleche et al proposed that CD8 T-cell recruitment to the GALT was mainly dependent upon integrin β7 and chemokine receptor CXCR3, while a limited CD4 and CD8 T-cell colocalization mediated by CCR6-dependent recruitment could contribute to poor viral control of the infection ( 59 ).…”
Section: Discussionsupporting
confidence: 92%
“…Such findings are concordant with studies of HIVinfected individuals which have also reported reduced frequencies of Th22 cells in these compartments [189][190][191], and this has been associated with damage towards the mucosal barrier and increased microbial translocation [191]. Although virologic suppression by ART does not restore the frequency of Th17 cells in the gut due to perturbations in the CCR6-CCL20 chemotactic axis [182][183][184], Th22 cells by contrast are reconstituted [182]. These cells preferentially home towards the gut in a CCL20-dependent manner but can migrate via the CCR10-CCL28 chemotactic axis as an alternative when CCL20 levels are reduced as in ARTsuppressed HIV-infected individuals.…”
Section: Th22 Cellssupporting
confidence: 85%
“…Importantly, sustained virologic suppression by ART does not restore the Th17 cell population in the gut in the majority of HIV-infected individuals [182]. Although these cells typically home towards the gut via the CCR6-CCL20 chemotactic axis, this is impaired in ART-suppressed, HIVinfected individuals as there is a decreased production of CCL20 by enterocytes in response to IFN-γ secretion by Th1 cells as well as IL-10 and TGF-β secretion by Tregs [183,184]. Recently, Th17 cells were found to be enriched in the inner foreskin of uninfected men compared to the outer foreskin [185].…”
Section: Th2 and Th9 Cellsmentioning
confidence: 99%
“…Primary small intestine epithelial cells were isolated and maintained in culture as previously described 11 12. Briefly, human intestinal tissues were obtained from resections of small bowel during elective surgery at the Digestive Surgery Department, Toulouse University Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Primary intestinal cells were differentiated as previously described 11 12. Briefly, cells were cultured on Transwell inserts (0.33 cm² area, 0.4 µm pore size, polyester membrane; Corning) covered with Matrigel (Corning).…”
Section: Methodsmentioning
confidence: 99%